HUBUNGAN KREATIVITAS MAHASISWA DENGAN HASIL BELAJAR PRAKTEK PADA MATA KULIAH PERAWATAN DAN PENATAAN RAMBUT PROGRAM STUDI PENDIDIKAN TATA RIAS DAN KECANTIKAN JURUSAN KESEJAHTERAAN KELUARGA FT UNP - Mentari, Mega; Rostamailis, Rostamailis; Rahmiati, Rahmiati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This study aims to reveal students' creative relationship with the learning outcomes at the course practice care and hair styling. This research is descriptive quantitative research that describes what the subject under study in order to obtain answers to questions of the problems studied. The population in this study were students of Make up and Beauty Family Welfare Department FT UNP listed in semester from January to June 2013, which amounted to 25 people, because the population is less than 100 then the entire population in this study the research sample. The data of this study consisted of primary data in the form of questionnaires and secondary data from a pure value students daily practice in the course of care and hair styling semesters from January to June 2013. Results of data analysis showed that the average score of respondents overall achievement of the variable creativity of 65.3% with a low category, the results of student learning practices with the highest level of achievement by 76% of respondents to a value between 71-80. Ha accepted hypothesis which states that there is a positive and significant relationship between student creativity with the practice of student learning outcomes at the course and treatment of hair styling with a correlation of 0.459 with the interpretation being while Ho is rejected. From the results of the study can be recommended for all elements related to the care and grooming of learning to improve student learning through the creative use of learning resources and effort learning strategies that lead to increased creativity in learning more.Kata Kunci : Memiliki rasa ingin tahu yang luas, percaya diri, bebas dalam berekspresi, dan dapat bekerja sendiri.